ROZKŁAD NORMALNY STÓP ZWROTU Z AKCJI WCHODZĄCYCH W SKŁAD NASTĘPUJĄCYCH INDEKSÓW GIEŁDOWYCH: WIG20, MWIG40 I SWIG80 - Borowski, Krzysztof (Metody Ilościowe w Badaniach Ekonomicznych, 2017)
The article verified the hypothesis regarding normal distribution of returns of shares - components of the following Warsaw Stock Exchange indexes Keywords: normal distribution, return rates, stock indices, ranking of companies